2016
DOI: 10.1088/1612-2011/13/10/105201
|View full text |Cite
|
Sign up to set email alerts
|

Intensity–intensity and intensity–amplitude correlation of microwave photons from a superconducting artificial atom

Abstract: We investigate the dynamics of the microwave-frequency nonclassical correlations in a three-level -configuration artificial atom, which is realized by superconducting quantum circuits. The intensity–intensity correlation and intensity field are strongly dependent on the relative phase of the driven fields. It is found that two interference loops are formed in the dressed state picture at or π, which are responsible for the generation of nonclassical microwave photons. When the phase is changed into or , the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…For the strong transition there is little deviation from the symmetry of the CHD correlation of a two-level atom [14,15] or a single-laser driven 3LA with electron shelving [16], where the small Hilbert space inhibits the asymmetry. Large asymmetric correlations have also been predicted for a 3LA in the ladder configuration [11], for a pair of Rydberg atoms with blockade effect [12], and for a superconducting artificial atom [13].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…For the strong transition there is little deviation from the symmetry of the CHD correlation of a two-level atom [14,15] or a single-laser driven 3LA with electron shelving [16], where the small Hilbert space inhibits the asymmetry. Large asymmetric correlations have also been predicted for a 3LA in the ladder configuration [11], for a pair of Rydberg atoms with blockade effect [12], and for a superconducting artificial atom [13].…”
Section: Introductionmentioning
confidence: 84%
“…Since the field's amplitude and intensity operators do not commute and have distinctive noise properties, timeasymmetric correlations, and hence non-Gaussian fluctuations (nonzero odd-order correlations) of the field, can be naturally detected by the AIC measurement scheme [8][9][10][11][12][13]. Indeed, asymmetric amplitude-intensity correlations were initially spotted in CHD simulations [2,8] and experiments [3] in cavity QED.…”
Section: Introductionmentioning
confidence: 99%
“…1: Scheme of the Λ three-level atom with spontaneous decay rates γa, γ b , interacting with lasers with Rabi frequencies Ωa, Ω b with detunings ∆a, ∆ b . asymmetry was readily observed for cavity QED systems both numerically [14,19] and experimentally [15], it has been the resonance fluorescence of several 3LA systems that have provided clear theoretical access to the understanding of the asymmetry [21][22][23][24][25][26]. More recent accounts of asymmetric correlations are found in plasmonics [27] and collective cavity QED [28].…”
Section: Introductionmentioning
confidence: 94%
“…Still more recently, Castro-Beltrán et al [38][39][40][41] undertook a thorough analytical treatment of non-Gaussian fluctuations encountered in resonance fluorescence of two-and three-level atomic systems via intensity-field correlation measurements. Further context-dependent studies on the subject have also been reported, such as the light emitted from a two-level atom in an optical cavity [42,43], superconducting artificial atoms [44], fluorescence from optical transitions in Ξ-and V-type three-level atoms [45,46], and the experimental realization of the resonance fluorescence of a single trapped 138 Ba + ion [47].…”
Section: Conditional Homodyne Detectionmentioning
confidence: 99%